Cardio-Ankle Vascular Index Reflects Impaired Exercise Capacity and Predicts Adverse Prognosis in Patients With Heart Failure - Watanabe, Koichiro; Yoshihisa, Akiomi; Sato, Yu; Hotsuki, Yu; Anzai, Fumiya; Ichijo, Yasuhiro; Kimishima, Yusuke; Yokokawa, Tetsuro; Misaka, Tomofumi; Sato, Takamasa; Kaneshiro, Takashi; Oikawa, Masayoshi; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aims: We aimed to clarify the associations of cardio-ankle vascular index (CAVI) with exercise capacity and prognosis in patients with heart failure (HF). Methods: We collected the clinical data of 223 patients who had been hospitalized for decompensated HF and had undergone both CAVI and cardiopulmonary exercise testing. Results: For the prediction of an impaired peak oxygen uptake (VO2) of < 14 mL/kg/min, receiver-operating characteristic curve demonstrated that the cutoff value of CAVI was 8.9. In the multivariate logistic regression analysis for predicting impaired peak VO2, high CAVI was found to be an independent factor (odds ratio 2.343, P = 0.045). We divided these patients based on CAVI: the low-CAVI group (CAVI < 8.9, n = 145) and the high-CAVI group (CAVI ≥ 8.9, n = 78). We compared patient characteristics and post-discharge cardiac events between the two groups. The high-CAVI group was older (69.0 vs. 58.0 years old, P < 0.001) and showed lower body mass index (23.0 vs. 24.1 kg/m2, P = 0.013). During the post-discharge follow-up period of median 1,623 days, 58 cardiac events occurred. The Kaplan–Meier analysis showed that the cardiac event rate was higher in the high-CAVI group than in the low-CAVI group (log–rank P = 0.004). In the multivariate Cox proportional hazard analysis, high CAVI was found to be an independent predictor of cardiac events (hazard ratio 1.845, P = 0.035). Conclusion: High CAVI is independently associated with impaired exercise capacity and a high cardiac event rate in HF patients.